Magnetic fields of the Kyiv underground: ecological aspect - Оrlyuk, М.I.; Romenets, А.O.; Orliuk, I.M. (Reports of the National Academy of Sciences of Ukraine, 2020)
The magnetic field is one of the significant environmental factors. Within megalopolises, technogenic magnetic fields often exceed permissible norms. This publication presents the results of studies of an alternating magnetic field of the technogenic origin in the Kyiv underground railway. For the first time, the technogenic component of the magnetic field was experimentally investigated in the frequency range of 10-3—10 Hz, during the movement of an electric train, with a wide range of measured values of the magnetic induction. It is shown that the sources of technogenic variations of tens and hundreds of microtesla are caused by changing fields, when electric motors are operating. The rhythm of abnormal values is determined by the mode of functioning and design of the undergroun. The revealed periods of peak values of the magnetic field correspond to the periods of regular pulsations of the geomagnetic field Pc1—Pc5, which are in the range 0.2—5…150—600 s. In accordance with the environmental norm, the exposed variations are harmonious by periods, and they exceed the variations of natural origin by several orders of magnitude by the intensity.